Effect of Gutta-percha Solvents on the Bond Strength of Sealers to Intraradicular Dentin: A Systematic Review - Ferreira, Ines; Braga, Ana Cristina; Pina-Vaz , Irene (Iranian Endodontic Journal, 2021)
Introduction: The aim of our systematic review was to assess the impact of gutta-percha solvents on the bond strength of endodontic sealers to intraradicular dentin using the push-out bond test. Methods and Materials: The literature was searched in databases (PubMed, Web of Science and Scopus) up to September 2020, using the following search terms: (bond strength AND solvent* AND sealer* AND (tooth root OR dentin OR retreatment OR root canal). No date limits were implemented, and English languages were included. The question research was constructed based on the PICO (Population, Intervention, Comparison, and Outcome) strategy: “Does gutta-percha solvents effect the bond strength of sealers to intraradicular dentin?”. The studies were analyzed by two reviewers and were included if they utilized extracted permanent human teeth with completely formed apices, as well as assessed the influence of gutta-percha solvents on the bond strength of sealers to intraradicular dentin using push-out bond test. Review articles, case reports and studies that included immature, bovine or artificial teeth were excluded. The risk of bias was evaluated based on the Cochrane criteria adopted to in vitro studies. Results: Thirty-two papers were analyzed, seven accomplished the eligibility criteria and were selected for our systematic review. The global risk of bias was high. Due to variations in the methodological variables, a meta-analysis could not be performed. Conclusion: Our systematic review highlighted the adverse effect of chloroform, which decreased the bond strength of different sealers, and the generally higher bond strength of epoxy resin-based sealers, detected with the push-out bond test. We recommend the standardization of methods in future studies to obtain a more definitive conclusion about the influence of solvents on the bond strength of sealers to intraradicular dentin.